Novel multi-layer multi-element bearing bush coating as well as preparation method and application thereof
By forming a multi-layer multi-coating layer on the bearing shell, including a boride layer, an AlSn40Cu layer and an Ag layer, the problems of high friction coefficient and poor embedding in the bimetal alloy bearing shell are solved, and the effects of reducing the friction coefficient, enhancing fatigue resistance and avoiding locking are achieved.
Patent Information
- Application Number
- CN202411911640.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The alloy layer in existing bimetal alloy bearing shells has a high friction coefficient and poor embedding ability, and is prone to lock after long-term work.
Using the preparation method of multi-layer multi-element bearing coating, a support functional layer, a transition functional layer and a self-lubricating layer are formed on the surface of the substrate, specifically including an in-situ self-generating boride layer, a periodically deposited AlSn40Cu layer and a deposited Ag layer, the structure is designed in a "hard and soft" mode.
Effectively inhibit the growth of Sn phase components in AlSn40Cu coating, improve binding force, reduce pressure between coatings, enhance fatigue resistance, reduce friction coefficient, avoid locking, and improve overall working life and reliability.
Smart Images

Figure CN119710612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of bearing bush coatings, and in particular to a novel multi-layered and multi-element bearing bush coating and a preparation method and application thereof. Background Art
[0002] The bearing is one of the most important and most intensive friction pairs in the transmission mechanism of the diesel engine power system. It is located between the journal and the bearing seat, and directly and indirectly contacts the journal during operation. It mainly supports the load and transmits the motion. However, under start-stop conditions, the bearing and the journal are prone to poor lubrication and heavy load, which leads to burning and increased wear. This requires the bearing to have good wear resistance and self-lubricating properties. Therefore, new bearing surface treatment technology and coating design are used to improve the wear resistance, load-bearing performance and anti-seizure of traditional bearing materials, which is an urgent need for the rapid development of advanced engines.
[0003] In the Chinese patent with application number 202410145562.9, the solid powder embedding boronization technology is used to prepare the in-situ self-generated boride layer. The preparation process is simple, the cost is low, and a good-quality, firmly bonded boride layer can be obtained. The friction coefficient gradually decreases with the increase of load (10N, 30N, 50N), which has great development prospects in heavy-load service environments; this patent improves the bonding strength by in-situ self-generated boride layer on the substrate surface, and has extremely strong wear resistance, but the coating is single and the hardness is too high. Using it in the diesel engine bearing will cause certain damage to the journal, which is not conducive to extending the overall service life of the engine; at the same time, the coating has a certain brittleness and insufficient self-lubricating performance. How to continue to design a soft coating with lubricating effect on its surface is extremely important.
[0004] In the Chinese patent with application number 201610712259.8, flame spraying technology is used to sequentially prepare soft and hard alternating composite coatings on the surface of the bearing material. The thickness of the Cu coating is 15-50μm, the thickness of the WC coating is 15-50μm, and the thickness of the MoS2 coating is 15-50μm, and the total thickness does not exceed 100μm. This soft and hard alternating composite coating consists of hard particles wrapped in a soft coating, and the hard coating improves the load-bearing capacity. There is a buffering effect between the coatings, which can effectively reduce and slow down the generation of cracks. The wear resistance and friction reduction performance of the bearing are improved, the bearing capacity of the bearing is improved, and the embedding performance of the bearing is improved, thereby improving the working life and anti-lock performance of the bearing. However, the coating structure prepared by this patent is strictly speaking "soft-hard-soft", and the data friction coefficient simulation results are excellent, but in actual applications, the role of the middle WC hard coating is not obvious, and the thermal expansion coefficients of the three coatings of Cu, WC and MoS2 are very different. The soft coating below the WC is prone to cracking under heavy load conditions, resulting in the inability to exert the excellent lubrication properties of the MoS2 coating above. The idea of "soft and hard" coating is good, but the coating selection, preparation technology selection and coating design selection still need to be improved; in addition, the preparation cost of this method is also very high and has no practical value.
[0005] In the Chinese patent with application number 201710879833.3, magnetron sputtering technology is used to prepare a composite coating of alternating layers of Ni transition layer, AlSn20Cu layer and Ag layer on the surface of steel / CuPb22Sn4 or steel / AlZn4SiPb bearings. This multi-layer design effectively relieves the stress of the coating, reduces the friction coefficient and wear rate, and enhances the fatigue resistance. However, even if the coating to which this patent belongs has a transition layer, the bonding force transition is still insufficient, and in actual working conditions, the surface coating quickly wears out or peels off, and the copper alloy layer below is soft and has a high friction coefficient, so it is still prone to locking, which reduces the service life.
[0006] In the Chinese patent with application number 202211348829.1, the electric spark alloying soft anti-friction coating process is used to prepare transition layers of Ag, Cu and Babbitt alloy coatings on the surface of the tin-bronze alloy bearing in sequence, which can effectively reduce the friction coefficient of the tin-bronze bearing surface and obtain a tin-bronze bearing with good surface comprehensive performance, excellent anti-friction performance, strong fatigue resistance, high reliability and good durability. However, the outermost layer of this patent is Babbitt alloy, which is an obsolete material, and the upper metal hardness is higher than the lower Ag and Cu metal hardness. The structure is "soft and hard", and the overall support layer is lacking. The bearing as a whole is prone to overall deformation under heavy load conditions, which seriously affects the working reliability and service life.
[0007] In the Chinese patent application number 201210498063.5, an organic / inorganic composite coating containing a solid lubricating phase is prepared on a copper-based bearing by a spraying method. The coating mainly includes a mixture of molybdenum disulfide, graphite, hexagonal boron nitride, cerium trifluoride, antimony trioxide, silicone resin and some organic solvents. The conventional copper-based metal bearing has problems such as poor lubrication performance, copper adhesion and insufficient wear resistance. The conventional copper-based metal bearing has problems such as poor lubrication performance, copper adhesion and insufficient wear resistance. Summary of the invention
[0008] The present invention designs and develops a novel multi-layered multi-element bearing shell coating, the purpose of the present invention is to solve the problems of high friction coefficient of the alloy layer in the existing bimetallic alloy bearing shell, poor embedding, and easy locking after long-term work.
[0009] The present invention designs and develops a novel method for preparing a multi-layered multi-element bearing coating. The purpose of the present invention is to introduce an in-situ autogenous boronizing layer with a load-bearing function and a composition gradient change during the preparation process, and to composite AlSn40Cu and Ag into a novel anti-friction and lubricating bearing coating material, and the structure is designed as a "hard-soft" mode.
[0010] The present invention designs and develops an application of a novel multi-layered multi-element bearing coating, the purpose of the present invention is to solve the application problems of high friction coefficient, poor wear resistance and embeddability of the alloy layer in the bimetallic alloy bearing of diesel engines, easy locking after long-term work, and prolonged working time.
[0011] The technical solution provided by the present invention is:
[0012] A novel method for preparing a multi-layered bearing coating comprises the following steps:
[0013] Step 1: burying the pretreated substrate in a boronizing agent, performing heat treatment, and forming a supporting functional layer after cooling;
[0014] Step 2: placing the substrate forming the supporting functional layer in the vacuum chamber of the ion beam assisted deposition device, setting the sputtering target to AlSn40Cu, adjusting the argon gas flow, voltage and current, cleaning the surface of the supporting functional layer after cooling by a low-energy ion source, turning on the target arc power supply to deposit the AlSn40Cu layer and then cooling it, and repeating the cleaning and deposition process for multiple times to form a transition functional layer;
[0015] Step 3: Replace the sputtering target with Ag, adjust the argon gas flow, voltage and current, clean the surface of the transition functional layer formed after cooling through a low-energy ion source, turn on the target arc power supply to deposit the Ag layer to form a self-lubricating layer and then cool it to obtain the novel multi-layer multi-element bearing coating;
[0016] Wherein, in the step 2 and the step 3, during the process of depositing the AlSn40Cu layer and the Ag layer, the sputtering target atoms are bombarded by a high energy ion source at the same time.
[0017] Preferably, in the step 1, the pretreatment process of the substrate includes: grinding the surface of the substrate with sandpaper, and then cleaning and drying it for standby use.
[0018] Preferably, in step 1, the heat treatment process includes:
[0019] Step 1, placing the boronizing agent in a crucible, heating and drying it, and then taking it out for standby use;
[0020] Step 2, burying the pretreated substrate in a boronizing agent to seal it, and placing it in a common box-type muffle furnace for heating;
[0021] Step 3: After the reaction is completed, wait for the sample to cool down to below 100°C with the furnace, and then take out the sample;
[0022] Step 4: Grind the sample to remove the boronizing agent remaining on the sample surface, and then clean and dry it; wherein the muffle furnace operating parameters should be set to gradually heat to 600-1000°C at a heating rate of 10°C / min, and keep warm for 20-200 minutes.
[0023] Preferably, in the step 2, the cleaning conditions include: cleaning time of 20 minutes, main arc voltage of 20 to 45 V, main arc current of 1.2 to 3.5 A, extraction voltage of 1.5 to 4.0 kV, extraction current of 50 to 200 mA; and
[0024] In the step three, the cleaning conditions include: cleaning time is 30 minutes, main arc voltage is 30V, main arc current is 2.0A, extraction voltage is 1.5kV, and extraction current is 100mA.
[0025] Preferably, in step 2, the sputtering conditions for depositing the AlSn40Cu layer include: a sputtering time of 60 to 100 min, a sputtering voltage of 800 V to 1200 V, a sputtering current of 0.5 A to 1.5 A, and a sputtering pressure of 3 to 15 × 10 -1 Pa; and
[0026] In step 3, the sputtering conditions for depositing the Ag layer include: sputtering time of 60 to 100 min, sputtering voltage of 1000 V, sputtering current of 1.1 A, and sputtering pressure of 1×10 -1 Pa.
[0027] Preferably, the conditions for high energy ion source bombardment sputtering AlSn40Cu target material include: bombardment stage time is 10min, main arc voltage is 40-65V, main arc current is 1.0-2.5A, extraction voltage is 6kV, extraction current is 62mA, acceleration voltage is 40-55kV, acceleration current is 4-18mA; and
[0028] The conditions for the high energy ion source bombardment sputtering of the Ag target include: the bombardment stage time is 10 min, the main arc voltage is 50 V, the main arc current is 1.5 A, the extraction voltage is 5 kV, the extraction current is 52 mA, the acceleration voltage is 50 kV, and the acceleration current is 10 mA.
[0029] Preferably, the thickness of the boride is 11-152 μm, the thickness of each layer of the AlSn40Cu layer is 2-3 μm, and the thickness of the Ag layer is 0.89-3.8 μm; and
[0030] The overall thickness of the AlSn40Cu layer is 2.6-18.5 μm.
[0031] A novel multi-layered multi-element bearing coating is prepared using the novel multi-layered multi-element bearing coating preparation method, comprising a supporting functional layer, a transition functional layer and a self-lubricating layer deposited in sequence;
[0032] Wherein, the supporting functional layer comprises a boride layer, the transition functional layer comprises an AlSn40Cu layer deposited periodically and multiple times, and the self-lubricating layer comprises a deposited Ag layer.
[0033] Preferably, the thickness of each AlSn40Cu layer is 2-3 μm, and the thickness of the Ag layer is 0.89-3.8 μm.
[0034] The invention discloses an application of a novel multi-layer and multi-element bearing shell coating in a bearing shell of a diesel engine, and uses the novel multi-layer and multi-element bearing shell coating.
[0035] The beneficial effects of the present invention are:
[0036] 1. The preparation method of the novel multi-layer multi-element bearing coating provided by the present invention effectively inhibits the growth of the Sn phase component in the AlSn40Cu coating by repeatedly depositing the AlSn40Cu coating, thereby improving the overall bonding force of the coating; at the same time, the multi-layer design is conducive to reducing the pressure between the coatings and enhancing the fatigue resistance; the boride coating is an in-situ autogenous infiltration layer, the preparation process is simple, the cost is low, and a good quality and firmly bonded infiltration layer can be obtained;
[0037] 2. In the novel multi-layer and multi-element bearing coating structure provided by the present invention, a boride layer of a certain thickness is introduced as a supporting functional layer. Especially under heavy load conditions, the surface coating is very easy to wear and peel off under start-stop conditions. The boride layer has an excellent friction coefficient, which can avoid the occurrence of locking to a certain extent, thereby improving the overall service life and reliability. The AlSn40Cu coating is used as a transition functional layer. On the one hand, it transitions the hardness of the lower boride coating and the upper Ag coating. On the other hand, it itself has certain lubrication properties, and the coating as a whole is not easy to be too hard. The coating should have a certain thickness to better protect the journal. The Ag coating has excellent self-lubricity, and the elastic modulus of the Ag particles is small. Its interface strengthening effect can be used to regulate the stress and brittleness of the overall coating in actual working conditions, further improving the anti-friction and anti-wear effect of the AlSn40Cu coating in actual working conditions. At the same time, the friction coefficient will gradually decrease with the increase of the load, and it has excellent anti-locking characteristics, which has great development prospects in the heavy-load service environment actually required by the bearing.
[0038] 3. The AlSn40Cu coating in the novel multi-layered multi-element bearing coating provided by the present invention is currently the most advanced composition in the aluminum-tin-copper coating of the bearing. When the tin content increases, the hardness and fatigue strength of the aluminum-tin alloy decrease to a certain extent, but the bite, embedding and compliance increase accordingly, the anti-bite load increases accordingly, and the wear of the journal decreases accordingly; and as for the coating itself, under dry friction conditions, tin can form a protective film on the shaft surface to overcome the rapid change of friction force, and will not cause the local area load of the bearing to increase sharply, and can better maintain the continuity of the lubricating oil film; the Ag coating in the novel multi-layered multi-element bearing coating provided by the present invention, the Ag wear debris generated in actual service can be used as a lubricating oil additive to reduce friction and wear under start-stop conditions;
[0039] 4. The AlSn40Cu coating in the novel multi-layered multi-element bearing coating provided by the present invention can not only reduce the wear of the bearing and the journal under oil lubrication conditions, but also, when starting and stopping in harsh environments such as heavy loads and high speeds, when the surface coating (AlSn40Cu+Ag) is severely worn, the boride coating will still have anti-lock performance, and has better applicability to actual working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a schematic diagram of the structure of the novel multi-layered multi-element bearing shell coating according to the present invention;
[0041] Figure 2 This is a flow chart of the preparation method of the novel multi-layered multi-element bearing coating of the present invention;
[0042] Figure 3a This is a SEM morphology of the outermost surface of the novel multi-layered multi-element bearing coating prepared in Example 1 of the present invention;
[0043] Figure 3b This is the EDS spectrum of the outermost surface of the novel multi-layered multi-element bearing coating prepared in Example 1 of the present invention;
[0044] Figure 4 A friction coefficient curve diagram of the novel multi-layered multi-element bearing coating prepared in Example 1 of the present invention after the friction test;
[0045] Figure 5 An optical microscope image of the wear scar of the novel multi-layered multi-element bearing coating prepared in Example 1 of the present invention after the friction test;
[0046] Figure 6 This is an optical microscope image of the grinding ball after the friction test of the novel multi-layered multi-element bearing coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0048] like Figure 1 As shown, the present invention provides a novel multi-layered multi-element bearing coating, comprising: a supporting functional layer 110, a transition functional layer 120 and a self-lubricating layer 130 coated on a steel plate substrate 100; wherein the supporting functional layer 110 specifically comprises an in-situ self-generated boride layer, the transition functional layer 120 specifically comprises a periodically multiple deposited AlSn40Cu layer, and the self-lubricating layer 130 specifically comprises a deposited Ag layer.
[0049] In another embodiment, the thickness of the boride is 52-152 μm, the thickness of each AlSn40Cu layer is 2-3 μm, and the thickness of the Ag coating is 0.89-3.8 μm.
[0050] In another embodiment, the overall thickness of the AlSn40Cu coating is 2.6-18.5 μm.
[0051] like Figure 2 As shown, the present invention provides a novel method for preparing a multi-layered multi-element bearing coating, comprising the following steps:
[0052] Step S100, pretreatment of the steel plate substrate 100: pretreatment of the steel plate substrate to be processed, grinding and polishing the surface of the substrate to meet the requirements of surface heat treatment and subsequent ion beam assisted deposition, and removing grease and impurities attached to the surface of the substrate;
[0053] Step S200, preparing boride 110: diffusing a boride layer of 11 to 152 μm on the surface of a pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method;
[0054] Step S300, preparing the AlSn40Cu coating 120: depositing a 2.6-18.5 μm multilayer transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology;
[0055] Step S400, preparing the Ag coating 130: depositing a 0.89-3.8 μm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology;
[0056] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0057] In another embodiment, the specific process of step S100 may include:
[0058] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0059] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0060] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0061] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0062] Step S105, placing the substrate in a 100°C oven to dry for 20 minutes, then taking it out and wrapping it with dust-free paper for later use.
[0063] In another embodiment, the specific process of step S200 may include:
[0064] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0065] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0066] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 600-1000° C. at a heating rate of 10° C. / min and keep warm for 20-200 min;
[0067] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0068] Step S205: polish the sample with 3000# sandpaper to remove the boronizing agent remaining on the sample surface. The surface should retain a certain degree of roughness to improve the bonding force of the next operation. At this time, the surface state of the sample should not affect the next ion beam assisted deposition operation;
[0069] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0070] Step S207: Finally, place the sample in a 100° C. oven and dry it for 20 minutes.
[0071] In another embodiment, the specific process of step S300 may include:
[0072] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0073] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0074] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 60 to 100 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0075] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 10 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0076] Step S304, repeating steps S302 to S303 one to eight times;
[0077] Step S305: After the above steps are completed, the furnace is cooled to room temperature.
[0078] In another embodiment, the specific process of step S400 may include:
[0079] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0080] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0081] Step S403: deposit a 1-2 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 60-100 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0082] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 10 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0083] Step S404: After the above steps are completed, the furnace is cooled to room temperature.
[0084] In another embodiment, the boride layer has a thickness of 52-82 μm.
[0085] In another embodiment, the thickness of the AlSn40Cu layer is 5.4-14.9 μm.
[0086] In another embodiment, the thickness of the Ag layer is 1.8-3.5 μm.
[0087] In another embodiment, the muffle furnace operating parameters should be set to gradually heat to 800-900° C. at a heating rate of 10° C. / min and keep warm for 30-50 minutes.
[0088] In another embodiment, in step S304, steps S302 to S303 are repeated three times.
[0089] The present invention will be further described below in conjunction with specific embodiments.
[0090] Example 1
[0091] The present invention provides a novel method for preparing a multi-layered bearing coating, comprising the following steps:
[0092] Step S100: Pretreatment of steel plate substrate:
[0093] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0094] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0095] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0096] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0097] Step S105, placing the substrate in a 100°C oven and drying for 20 minutes, then taking it out and wrapping it with dust-free paper for later use;
[0098] Step S200, a 52 μm boride layer is diffused on the surface of the pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method:
[0099] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0100] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0101] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 800° C. at a heating rate of 10° C. / min and keep warm for 50 minutes;
[0102] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0103] Step S205, grinding the sample with 3000# sandpaper to remove the boronizing agent remaining on the surface of the sample;
[0104] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0105] Step S207, finally placing the sample in a 100° C. oven to dry for 20 minutes;
[0106] Step S300, depositing five layers of 11.8 μm transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology:
[0107] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0108] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0109] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 70 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0110] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 10 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0111] Step S304, repeat steps S302 to S303 five times;
[0112] Step S305: After the above steps are completed, the furnace is cooled to room temperature;
[0113] Step S400: Depositing a 1.8 μm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology:
[0114] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0115] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0116] Step S403: deposit a 1-2 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 70 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0117] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 10 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0118] Step S404: After the above steps are completed, the furnace is cooled to room temperature;
[0119] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0120] Example 2
[0121] The present invention provides a novel method for preparing a multi-layered bearing coating, comprising the following steps:
[0122] Step S100: Pretreatment of steel plate substrate:
[0123] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0124] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0125] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0126] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0127] Step S105, placing the substrate in a 100°C oven and drying for 20 minutes, then taking it out and wrapping it with dust-free paper for later use;
[0128] Step S200, a 74 μm boride layer is diffused on the surface of the pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method:
[0129] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0130] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0131] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 900° C. at a heating rate of 10° C. / min and keep warm for 50 minutes;
[0132] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0133] Step S205, grinding the sample with 3000# sandpaper to remove the boronizing agent remaining on the surface of the sample;
[0134] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0135] Step S207, finally placing the sample in a 100° C. oven to dry for 20 minutes;
[0136] Step S300, depositing two layers of 5.4 μm transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology:
[0137] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0138] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0139] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 70 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0140] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 10 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0141] Step S304, repeat steps S302 to S303 twice;
[0142] Step S305: After the above steps are completed, the furnace is cooled to room temperature;
[0143] Step S400: Depositing a 3.8 μm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology:
[0144] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0145] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0146] Step S403: deposit a 3-4 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 70 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0147] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 10 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0148] Step S404: After the above steps are completed, the furnace is cooled to room temperature;
[0149] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0150] Example 3
[0151] The present invention provides a novel method for preparing a multi-layered bearing coating, comprising the following steps:
[0152] Step S100: Pretreatment of steel plate substrate:
[0153] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0154] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0155] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0156] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0157] Step S105, placing the substrate in a 100°C oven and drying for 20 minutes, then taking it out and wrapping it with dust-free paper for later use;
[0158] Step S200, a 82 μm boride layer is diffused on the surface of the pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method:
[0159] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0160] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0161] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 1000° C. at a heating rate of 10° C. / min and keep warm for 100 minutes;
[0162] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0163] Step S205, grinding the sample with 3000# sandpaper to remove the boronizing agent remaining on the surface of the sample;
[0164] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0165] Step S207, finally placing the sample in a 100° C. oven to dry for 20 minutes;
[0166] Step S300, depositing eight layers of 18.5 μm transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology:
[0167] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0168] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0169] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 80 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0170] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 10 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0171] Step S304, repeat steps S302 to S303 eight times;
[0172] Step S305: After the above steps are completed, the furnace is cooled to room temperature;
[0173] Step S400: Depositing a 1.8 μm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology:
[0174] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0175] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0176] Step S403: deposit a 1-2 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 80 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0177] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 10 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0178] Step S404: After the above steps are completed, the furnace is cooled to room temperature;
[0179] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0180] Example 4
[0181] The present invention provides a novel method for preparing a multi-layered bearing coating, comprising the following steps:
[0182] Step S100: Pretreatment of steel plate substrate:
[0183] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0184] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0185] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0186] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0187] Step S105, placing the substrate in a 100°C oven and drying for 20 minutes, then taking it out and wrapping it with dust-free paper for later use;
[0188] Step S200: a 57 μm boride layer is diffused on the surface of the pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method:
[0189] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0190] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0191] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 900° C. at a heating rate of 10° C. / min and keep warm for 30 minutes;
[0192] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0193] Step S205, grinding the sample with 3000# sandpaper to remove the boronizing agent remaining on the surface of the sample;
[0194] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0195] Step S207, finally placing the sample in a 100° C. oven to dry for 20 minutes;
[0196] Step S300, depositing a 2.6 μm transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology:
[0197] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0198] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0199] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 80 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0200] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 10 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0201] Step S304, repeat steps S302 to S303 once;
[0202] Step S305: After the above steps are completed, the furnace is cooled to room temperature;
[0203] Step S400, depositing a 890nm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology:
[0204] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0205] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0206] Step S403: deposit a 1 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 80 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0207] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 10 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0208] Step S404: After the above steps are completed, the furnace is cooled to room temperature;
[0209] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0210] Example 5
[0211] The present invention provides a novel method for preparing a multi-layered bearing coating, comprising the following steps:
[0212] Step S100: Pretreatment of steel plate substrate:
[0213] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0214] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0215] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0216] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0217] Step S105, placing the substrate in a 100°C oven and drying for 20 minutes, then taking it out and wrapping it with dust-free paper for later use;
[0218] Step S200, a 11 μm boride layer is diffused on the surface of the pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method:
[0219] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0220] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0221] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 600° C. at a heating rate of 10° C. / min and keep warm for 20 minutes;
[0222] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0223] Step S205, grinding the sample with 3000# sandpaper to remove the boronizing agent remaining on the surface of the sample;
[0224] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0225] Step S207, finally placing the sample in a 100° C. oven to dry for 20 minutes;
[0226] Step S300, depositing three layers of 7.6 μm transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology:
[0227] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0228] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0229] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 60 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0230] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 10 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0231] Step S304, repeat steps S302 to S303 three times;
[0232] Step S305: After the above steps are completed, the furnace is cooled to room temperature;
[0233] Step S400: Depositing a 2.6 μm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology:
[0234] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0235] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0236] Step S403: deposit a 2-3 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 60 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0237] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 10 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0238] Step S404: After the above steps are completed, the furnace is cooled to room temperature;
[0239] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0240] Example 6
[0241] The present invention provides a novel method for preparing a multi-layered bearing coating, comprising the following steps:
[0242] Step S100: Pretreatment of steel plate substrate:
[0243] Step S101, polish the surface with 100#, 400#, 1000#, and 2000# sandpaper in sequence;
[0244] Step S102, placing the polished steel plate substrate in a pollution-free acetone solution for ultrasonic cleaning for 10 minutes, taking it out and wiping it clean with a clean silk cloth;
[0245] Step S103, placing the substrate in a 100° C. oven and drying for 10 minutes;
[0246] Step S104, the substrate is further placed in a non-polluting alcohol solution for ultrasonic cleaning for 20 minutes, and is taken out and wiped clean with a clean silk cloth; when wiping dry, the polished surface of the substrate is wiped in the same direction to ensure that there is no water stain or impurity residue on the surface of the substrate;
[0247] Step S105, placing the substrate in a 100°C oven and drying for 20 minutes, then taking it out and wrapping it with dust-free paper for later use;
[0248] Step S200, a 152 μm boride layer is diffused on the surface of the pretreated steel plate substrate by a chemical heat treatment solid phase boronizing method:
[0249] Step S201, placing a boronizing agent in a crucible according to a fixed ratio, placing the crucible and the instrument in a 150° C. oven for drying for 60 minutes, and taking them out for standby use after drying; the boronizing agent is a commercial solid-phase boronizing agent mixed in a certain ratio;
[0250] Step S202, burying the pretreated substrate in a boronizing agent according to the proportion of the boronizing agent, and sealing it in a ceramic crucible;
[0251] Step S203, placing the sealed crucible into a common box-type muffle furnace and placing it in the center of the box; wherein the muffle furnace operating parameters should be set to gradually heat to 1000° C. at a heating rate of 10° C. / min and keep warm for 200 minutes;
[0252] Step S204: After the reaction is completed, wait for the sample to cool down to below 100° C. with the furnace, and then take out the sample;
[0253] Step S205, grinding the sample with 3000# sandpaper to remove the boronizing agent remaining on the surface of the sample;
[0254] Step S206, placing the polished sample in an alcohol solution for ultrasonic cleaning for 20 minutes;
[0255] Step S207, finally placing the sample in a 100° C. oven to dry for 20 minutes;
[0256] Step S300, depositing six layers of 14.9 μm transitional functional AlSn40Cu coating on the boride layer described in S200 by ion beam assisted deposition technology:
[0257] Step S301, install the sample after chemical heat treatment and solid phase boronization on the fixture, and place the whole in the vacuum chamber of the ion beam assisted deposition device, and introduce argon gas into the vacuum chamber as a protective gas. Before taking out the sample, the argon gas should be continuously circulated, and its working gas pressure is 1-5Pa, and the purity of the argon gas is 99.9%;
[0258] Step S302, using a low-energy ion source to clean the surface of the sample: the low-energy ion source is used to clean the surface of the sample for 20 minutes, wherein the main arc voltage is 20-45V, the main arc current is 1.2-3.5A, the extraction voltage is 1.5-4.0kV, and the extraction current is 50-200mA;
[0259] Step S303: deposit an AlSn40Cu coating with a thickness of 2 to 3 μm on the surface of the sample by magnetron sputtering; the sputtering time is 100 min, the sputtering voltage is 800 V to 1200 V, the sputtering current is 0.5 A to 1.5 A, and the sputtering pressure is 3 to 15×10 -1 Pa;
[0260] At the same time, the sample is subjected to an ion-assisted process using a high-energy ion source, and the high-energy ion source bombardment stage is 240 minutes; wherein, the main arc voltage is 40-65V, the main arc current is 1.0-2.5A, the extraction voltage is 6kV, the extraction current is 62mA, the acceleration voltage is 40-55kV, and the acceleration current is 4-18mA. After the argon ions of the high-energy ion source are accelerated by a high-voltage electric field, they collide with the target material atomic groups, so that they obtain high energy, and finally accelerate to bombard the surface of the boride layer to nucleate and grow, so as to improve the bonding force between the AlSn40Cu layer and the underlying boride layer, and improve the overall deposition quality of the film layer;
[0261] Step S304, repeat steps S302 to S303 six times;
[0262] Step S305: After the above steps are completed, the furnace is cooled to room temperature;
[0263] Step S400: Depositing a 3.5 μm self-lubricating Ag coating on the AlSn40Cu layer described in S300 by ion beam assisted deposition technology:
[0264] Step S401, after step S304 is completed, the sample on the fixture is not moved, the sputtering target is replaced with Ag, and argon gas is introduced into the vacuum chamber of the ion beam assisted deposition device as a protective gas. The argon gas should be continuously circulated before the sample is taken out, and the working gas pressure is 3Pa, and the purity of the argon gas is 99.9%;
[0265] Step S402, using a low-energy ion source to clean the sample surface: the low-energy ion source is used to clean the sample surface for 30 minutes; wherein the main arc voltage is 30V, the main arc current is 2.0A, the extraction voltage is 1.5kV, and the extraction current is 100mA;
[0266] Step S403: deposit a 3-4 μm thick Ag coating on the surface of the sample by magnetron sputtering; the sputtering time is 100 min, the sputtering voltage is 1000 V, the sputtering current is 1.1 A, and the sputtering pressure is 1×10 -1 Pa;
[0267] At the same time, the sample was subjected to an ion-assisted process using a high-energy ion source. The high-energy ion source bombardment stage was 120 minutes, wherein the main arc voltage was 50 V, the main arc current was 1.5 A, the extraction voltage was 5 kV, the extraction current was 52 mA, the acceleration voltage was 50 kV, and the acceleration current was 10 mA. After the argon ions of the high-energy ion source were accelerated by a high-voltage electric field, they collided with the target material atomic groups, so that they acquired high energy, and finally accelerated to bombard the surface of the AlSn40Cu layer to nucleate and grow, so as to improve the bonding force between the Ag layer and the AlSn40Cu layer below, and improve the overall deposition quality of the film layer.
[0268] Step S404: After the above steps are completed, the furnace is cooled to room temperature;
[0269] Step S500, sealing of the final novel multi-layered multi-element bearing coating sample: after the boride / AlSn40Cu / Ag composite coating is formed on the surface, the sample is covered with degreasing paper and dust-free paper, and then vacuum-sealed for storage.
[0270] Test Case
[0271] In the present invention, by adjusting the heating temperature and the holding time of the muffle furnace and the sputtering time during the deposition of the AlSn40Cu layer and the deposition of the Ag layer, a coating material with a lower friction coefficient can be obtained. The test example is as follows:
[0272] The bearing samples in Example 1 were taken for SEM, friction and wear, and optical microscopy testing and characterization: the equipment model of the optical microscope was DM6000M, the equipment model of the scanning electron microscope was SU5000, and the equipment model of the friction and wear testing machine was MS-T3000; wherein, when the friction and wear analysis of the samples was performed by the friction and wear tester, the friction and wear tester was preheated for 20 minutes at room temperature, the same air humidity and oil lubrication environment, and the test was performed under the oil lubrication test conditions of Φ5mm sliding distance, 15N load, 200r / min rotation speed, and 60min test time.
[0273] like Figure 3a , Figure 3b As shown, the EDS spectrum results of area 1 prove that the outermost layer is Ag, and the surface Ag coating is dense, relatively uniform, and presents obvious granularity.
[0274] like Figure 4 As shown, the friction and wear analysis of the bearing coating surface was carried out by a friction and wear tester. The friction and wear tester was preheated for 20 minutes at room temperature and air humidity, and the test was carried out under the test conditions of oil lubrication, high load and high speed. The friction coefficient was at an extremely low level at the beginning. After 60 minutes of testing, the average friction coefficient was extremely low, only 0.1180.
[0275] like Figure 5 As shown in the figure, the width of the wear scar is only about 285.7 μm, the wear scar surface is relatively smooth, has a certain degree of fit, and the surface Ag coating has an obvious self-lubricating effect.
[0276] like Figure 6 As shown, due to the influence of the lubricating fluid environment, the wear marks on the grinding ball surface are irregular, but no obvious wear occurs.
[0277] The friction and wear test in Example 1 was maintained for 60 minutes, and the average friction coefficient was 0.1180; the friction and wear test in Example 2 was maintained for 60 minutes, and the average friction coefficient was 0.1320; the friction and wear test in Example 3 was maintained for 80 minutes, and the average friction coefficient was 0.1460; the friction and wear test in Example 4 was maintained for 15 minutes, and the friction coefficient rose rapidly, and the lubricating layer and the functional layer coating were too thin as a whole. After continuing for 90 minutes, the friction coefficient was maintained at 0.290, but no emergency stop occurred; the friction and wear test in Example 5 was maintained for 60 minutes, and the average friction coefficient was 0.1290; the friction and wear test in Example 6 was maintained for 60 minutes, and the average friction coefficient was 0.1190; the above embodiments can prove that the new multi-layer multi-element bearing coating provided by the present invention can significantly reduce the friction coefficient, has good embedding properties, reduces the risk of locking, and improves service life and reliability at work.
[0278] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a novel multi-layered multi-element bearing coating, characterized in that: The steps include: Step 1: burying the pretreated substrate in a boronizing agent, performing heat treatment, and forming a supporting functional layer after cooling; Step 2: placing the substrate forming the supporting functional layer in the vacuum chamber of the ion beam assisted deposition device, setting the sputtering target to AlSn40Cu, adjusting the argon gas flow, voltage and current, cleaning the surface of the supporting functional layer after cooling by a low-energy ion source, turning on the target arc power supply to deposit the AlSn40Cu layer and then cooling it, and repeating the cleaning and deposition process for multiple times to form a transition functional layer; Step 3: Replace the sputtering target with Ag, adjust the argon gas flow, voltage and current, clean the surface of the transition functional layer formed after cooling through a low-energy ion source, turn on the target arc power supply to deposit the Ag layer to form a self-lubricating layer and then cool it to obtain the novel multi-layer multi-element bearing coating; Wherein, in the step 2 and the step 3, during the process of depositing the AlSn40Cu layer and the Ag layer, the sputtering target atoms are bombarded by a high energy ion source at the same time.
2. The method for preparing the novel multi-layered multi-element bearing coating according to claim 1, characterized in that: In the step 1, the pretreatment process of the substrate includes: grinding the surface of the substrate with sandpaper, and then cleaning and drying it for standby use.
3. The method for preparing the novel multi-layered multi-element bearing coating according to claim 1 or 2, characterized in that: In the step 1, the heat treatment process includes: Step 1, placing the boronizing agent in a crucible, heating and drying it, and then taking it out for standby use; Step 2, burying the pretreated substrate in a boronizing agent to seal it, and placing it in a common box-type muffle furnace for heating; Step 3: After the reaction is completed, wait for the sample to cool down to below 100°C with the furnace, and then take out the sample; Step 4: polish the sample to remove the boronizing agent remaining on the sample surface, and then clean and dry it; The muffle furnace operating parameters should be set to gradually heat to 600-1000°C at a heating rate of 10°C / min and keep warm for 20-200min.
4. The method for preparing the novel multi-layered multi-element bearing coating according to claim 1, characterized in that: In the step 2, the cleaning conditions include: cleaning time is 20 minutes, main arc voltage is 20-45V, main arc current is 1.2-3.5A, extraction voltage is 1.5-4.0kV, extraction current is 50-200mA; and In the step three, the cleaning conditions include: cleaning time is 30 minutes, main arc voltage is 30V, main arc current is 2.0A, extraction voltage is 1.5kV, and extraction current is 100mA.
5. The method for preparing the novel multi-layered multi-element bearing coating according to claim 4, characterized in that: In the step 2, the sputtering conditions for depositing the AlSn40Cu layer include: a sputtering time of 60 to 100 min, a sputtering voltage of 800 V to 1200 V, a sputtering current of 0.5 A to 1.5 A, and a sputtering pressure of 3 to 15 × 10 -1 Pa; and In step 3, the sputtering conditions for depositing the Ag layer include: sputtering time of 60 to 100 min, sputtering voltage of 1000 V, sputtering current of 1.1 A, and sputtering pressure of 1×10 -1 Pa.
6. The method for preparing the novel multi-layered multi-element bearing coating according to claim 5, characterized in that: The conditions for the high energy ion source bombardment sputtering of AlSn40Cu target material include: bombardment stage time of 10 minutes, main arc voltage of 40-65V, main arc current of 1.0-2.5A, extraction voltage of 6kV, extraction current of 62mA, acceleration voltage of 40-55kV, acceleration current of 4-18mA; and The conditions for the high energy ion source bombardment sputtering of the Ag target include: the bombardment stage time is 10 min, the main arc voltage is 50 V, the main arc current is 1.5 A, the extraction voltage is 5 kV, the extraction current is 52 mA, the acceleration voltage is 50 kV, and the acceleration current is 10 mA.
7. The method for preparing the novel multi-layered multi-element bearing coating according to any one of claims 1, 2, 4-6, characterized in that: The thickness of the boride is 11 to 152 μm, the thickness of each AlSn40Cu layer is 2 to 3 μm, and the thickness of the Ag layer is 0.89 to 3.8 μm; and The overall thickness of the AlSn40Cu layer is 2.6-18.5 μm.
8. A novel multi-layered bearing coating, characterized in that: It is prepared by using the preparation method of the novel multi-layered bearing coating according to any one of claims 1 to 7, comprising a supporting functional layer, a transition functional layer and a self-lubricating layer deposited in sequence; Wherein, the supporting functional layer comprises a boride layer, the transition functional layer comprises an AlSn40Cu layer deposited periodically and multiple times, and the self-lubricating layer comprises a deposited Ag layer.
9. The novel multi-layered bearing coating according to claim 8, characterized in that: The thickness of each AlSn40Cu layer is 2-3 μm, and the thickness of the Ag layer is 0.89-3.8 μm.
10. Application of a novel multi-layered multi-element bearing coating in a diesel engine bearing, characterized in that: Use the novel multi-layered bearing coating as claimed in claim 8.
Citation Information
Patent Citations
Method for preparing solid lubricant coating on copper base bearing bush
CN103849311A
Alternating Hard and Soft Composite Coating for Bearing Material Surface and its Preparation Method
CN106222656B
All-metal self-lubricating and friction-reducing coating for bearing bushes and its preparation method
CN107699859B
Tin bronze bearing bush surface electric spark alloying soft antifriction coating process
CN115679319A
Low-temperature preparation method of high-wear-resistance boride infiltrated layer on surface of GH4169 alloy
CN118048602A